2010
DOI: 10.1167/iovs.10-5666
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Distribution in the Human Eye: Relevance to the Etiology of Open-Angle Glaucoma after Vitrectomy

Abstract: Oxygen metabolism by the lens and cornea establishes oxygen gradients in the anterior segment. Vitrectomy and cataract surgery increase pO(2) in the anterior chamber angle, potentially damaging trabecular meshwork cells. We propose that oxygen levels in the anterior chamber angle are strongly influenced by oxygen derived from the ciliary body circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
147
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(158 citation statements)
references
References 53 publications
9
147
0
2
Order By: Relevance
“…In any case, oxidative metabolism by superficial lens cells should assure that oxygen levels in the deeper fibre cells are much lower than near the lens surface. This prediction is supported by measurements of oxygen gradients across the lens in rabbits [27] and in the human lens nucleus [24], as well as by much higher pO 2 anterior to the lens after cataract surgery and intraocular lens implantation, when the superficial tissues at the anterior of the lens have been removed [22].…”
Section: The Mechanisms That Maintain the Low-oxygen Environment Aroumentioning
confidence: 74%
See 3 more Smart Citations
“…In any case, oxidative metabolism by superficial lens cells should assure that oxygen levels in the deeper fibre cells are much lower than near the lens surface. This prediction is supported by measurements of oxygen gradients across the lens in rabbits [27] and in the human lens nucleus [24], as well as by much higher pO 2 anterior to the lens after cataract surgery and intraocular lens implantation, when the superficial tissues at the anterior of the lens have been removed [22].…”
Section: The Mechanisms That Maintain the Low-oxygen Environment Aroumentioning
confidence: 74%
“…3% O 2 ) [19,20], a value that is close to the normal level of oxygen in most tissues. In the vitreous near the posterior of the human lens, the pO 2 drops to approximately 7 mmHg (approx.1% O 2 ) [21] and our recent measurements in human patients revealed that the pO 2 near the anterior and lateral surfaces of the lens is typically about 3 mmHg (less than 0.4%) [22]. The low oxygen near the surfaces of the lens and the consumption of oxygen by lens cells results in even lower pO 2 in the lens nucleus [23,24].…”
Section: Oxygen Toxicitymentioning
confidence: 79%
See 2 more Smart Citations
“…The asterisk indicates thickening of the retinal nerve fibre layer in the temporal position of the right eye due to macular pucker formation (bottom). (Chang 2006;Siegfried et al 2010). Post-PPV glaucoma was shown to occur in up to 20% (Chang 2006).…”
Section: Referencesmentioning
confidence: 99%